Correction to: Direct photo-oxidation and superoxide radical as major responsible for dye photodegradation mechanism promoted by TiO2–rGO heterostructure - Byzynski, Gabriela [UNESP]; Volanti, Diogo P. [UNESP]; Ribeiro, Cauê; Mastelaro, Valmor R.; Longo, Elson (Springer Nature, 2018)
The original version of this article contains a missed citation in the Material and Methods Section, GO synthesis.